Preparation of Tyrosylprotein Sulfotransferases for In Vitro One-Pot Enzymatic Synthesis of Sulfated Proteins/Peptides - Wang, Chen-Chu (ACS Omega, 2018)
[Image: see text] Protein tyrosine sulfation (PTS), catalyzed by membrane-anchored tyrosylprotein sulfotransferase (TPST), is one of the most common post-translational modifications of secretory and transmembrane proteins. PTS, a key modulator of extracellular protein–protein interactions, accounts for various important biological activities, namely, virus entry, inflammation, coagulation, and sterility. The preparation and characterization of TPST is fundamental for understanding the synthesis of tyrosine-sulfated proteins and for studying PTS in biology. A sulfated protein was prepared using a TPST-coupled protein sulfation system that involves the generation of the active sulfate 3′-phosphoadenosine-5′-phosphosulfate (PAPS) through either PAPS synthetase (PAPSS) or phenol sulfotransferase. The preparation of sulfated proteins was confirmed through radiometric or immunochemical assays. In this study, enzymatically active Drosophila melanogaster TPST (DmTPST) and human TPSTs (hTPST1 and hTPST2) were expressed in Escherichia coli BL21(DE3) host cells and purified to homogeneity in high yield. Our results revealed that recombinant DmTPST was particularly useful considering its catalytic efficiency and ease of preparation in large quantities. This study provides tools for high-efficiency, one-step synthesis of sulfated proteins and peptides that are useful for further deciphering the mechanisms, functions, and future applications of PTS.